Rapid depletion of "catch-and-release" anti-ASGR1 antibody in vivo - Siva Charan Devanaboyina; Peng Li; Edward L. LaGory; Carrie Poon-Andersen; Kevin D. Cook; Marcus Soto; Zhe Wang; Khue Dang; Craig Uyeda; Ryan B. Case; Veena A. Thomas; Ronya Primack; et al. (Taylor & Francis Group, 2024)
Targeting antigens with antibodies exhibiting pH/Ca2+-dependent binding against an antigen is an attractive strategy to mitigate target-mediated disposition and antigen buffering. Studies have reported improved serum exposure of antibodies exhibiting pH/Ca2+-binding against membrane-bound receptors. Asialoglycoprotein receptor 1 (ASGR1) is a membrane-bound receptor primarily localized in hepatocytes. With a high expression level of approximately one million receptors per cell, high turnover, and rapid recycling, targeting this receptor with a conventional antibody is a challenge. In this study, we identified an antibody exhibiting pH/Ca2+-dependent binding to ASGR1 and generated antibody variants with increased binding to neonatal crystallizable fragment receptor (FcRn). Serum exposures of the generated anti-ASGR1 antibodies were analyzed in transgenic mice expressing human FcRn. Contrary to published reports of increased serum exposure of pH/Ca2+-dependent antibodies, the pH/Ca2+-dependent anti-ASGR1 antibody had rapid serum clearance in comparison to a conventional anti-ASGR1 antibody. We conducted sub-cellular trafficking studies of the anti-ASGR1 antibodies along with receptor quantification analysis for mechanistic understanding of the rapid serum clearance of pH/Ca2+-dependent anti-ASGR1 antibody. The findings from our study provide valuable insights in identifying the antigens, especially membrane bound, that may benefit from targeting with pH/Ca2+-dependent antibodies to obtain increased serum exposure.